Large adnexal mass: is laparoscopic surgery a safe option? - Talwar, Prathap; Talwar, Karishma; C. A., Pranidha Shree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Laparoscopic surgery is regarded as the gold standard for management of adnexal tumours due to many advantages. Currently, the exact size of the adnexal tumour contraindicating laparoscopic management has not been clearly defined. Some studies suggest laparotomy for the treatment of adnexal tumours larger than 8 to 10 cm. Risk of malignancy increases with large cysts. Issues with operation of huge adnexal masses are limited surgical field, difficulty in inserting trocars and removing the specimen without rupture. This study aims to evaluate the feasibility and surgical outcomes of laparoscopic surgery for large adnexal masses. Methods: A prospective observational study was conducted in the Department of Obstetrics and Gynaecology, JSS Medical College, Mysuru. Results: 35 patients with large adnexal masses, which were thought to be benign, were subjected to laparoscopic surgery. Mean diameter of masses as per the pre-operative ultrasound measurements was 12.2cm (range: 10.1-20.4cm). The mean operative time was 51.15minutes, estimated blood loss was 85.4ml, duration of postoperative hospital stay was 2.8 days. Serous cystadenoma was the most common histopathological finding. However, one case of borderline tumour was found. Conclusions: The potential risk of malignancy is the most important limiting factor for laparoscopic management of large ovarian cysts. Therefore, it is necessary to establish risk profiles of patients with adnexal masses in order to benefit from minimally invasive surgery wherever possible. The current study supports laparoscopic management of large ovarian cysts as a technically feasible method if proper case selection is made.